Three new free-living marine nematode species of Dorylaimopsis (Nematoda: Araeolaimida: Comesomatidae) from the South China Sea and the Chukchi Sea - Fu, Sujing; Leduc, Daniel; Rao, Yiyong; Cai, Lizhe (Zootaxa, 2019)
Three new species of the free-living marine nematode genus Dorylaimopsis are described from the South China Sea and the Chukchi Sea. Dorylaimopsis longispicula sp. n. is characterized by cuticle with lateral differentiation consisting of four longitudinal rows of larger dots in pharyngeal and tail regions, two rows of larger dots elsewhere, long curved spicules, and 12–16 tubular precloacal supplements. Dorylaimopsis boucheri sp. n. is characterized by lateral differentiation consisting of 3–4 longitudinal rows of larger dots in males and 4–6 rows in females, beginning about 30 μm posterior to amphids and terminating at the conical portion of the tail, 13–16 tubular precloacal supplements, and distal part of tail cylindrical without terminal setae. Dorylaimopsis jinyuei sp. n. is characterized by cuticle with lateral differentiation in the form of longitudinal rows of larger dots in two separate regions, not along entire body. One region is from posterior edge of amphid to anterior of intestine or anterior border of pharyngeal bulb in some females (4–7 longitudinal rows), the other is the tail region (5–7 longitudinal rows). In this paper, Dorylaimopsis metatypica Chitwood, 1936 is transferred to Hopperia because it is characterized by lateral differentiation consisting of larger, irregularly-distributed coarse dots (as in Hopperia), and Hopperia communis Gagarin & Nguyen, 2006 is transferred to Dorylaimopsis based on the presence of longitudinal rows of coarse dots and a cylindrical buccal cavity in most specimens of this species. A dichotomous key to valid species of Dorylaimopsis Ditlevsen, 1918 is provided.